Good Corporate Governance in Implementing Corporate Social Responsibility at the State-Owned Enterprise PT. Antam UBPN Kolaka - Said, Achmad Lamo; Djabbari, Muhammad Hidayat; Azis, La Ode Asrun; Hidayat, Rahmat (Universitas Padjadjaran, 2025)
The Corporate Social Responsibility (CSR) program of PT. Antam UBPN Kolaka is an essential part of the company's efforts to fulfill its social and environmental responsibilities in line with the principles of Good Corporate Governance (GCG). However, challenges in applying GCG principles in the CSR program, such as transparency, accountability, independence, and fairness, still need further examination, particularly in the context of uneven program distribution. This study purposed to analyze the application of Good Corporate Governance principles in implementing Corporate Social Responsibility programs at Antam UBPN Kolaka. The main focus of this research was on the principles of transparency, accountability, responsibility, independence, and fairness in CSR management. The research method employed is a qualitative approach with data analysis through interviews, observations, and documentation. The results indicated that Antam UBPN Kolaka has been consistently applying GCG principles in its CSR programs, with particular attention to community and government involvement, as well as fair and proportional distribution of benefits. The application of these principles reflects transparent and accountable governance, oriented toward social sustainability. This study concludes that Antam UBPN Kolaka has successfully built CSR governance that aligns with GCG principles, although there are still shortcomings in terms of the distribution gap, limited access to information for the community, and the influence of external pressures that may affect the objectivity of the CSR program.